Heidegger's Poietic Writings : From Contributions to Philosophy to The Event - Vallega-Neu, Daniela, 1966- (Book collections on Project MUSE., 2018)
Engaging the development of Heidegger's non-public writings on the event between 1936 and 1941, Daniela Vallega-Neu reveals what Heidegger's private writings kept hidden. Vallega-Neu takes readers on a journey through these volumes, which are not philosophical works in the traditional sense as they read more like fragments, collections of notes, reflections, and expositions. In them, Vallega-Neu sees Heidegger searching for a language that does not simply speak about being, but rather allows a sense of being to emerge in his thinking and saying. She focuses on striking shifts in the tone and movement of Heidegger's thinking during these important years. Skillfully navigating the unorthodox and intimate character of these writings, Vallega-Neu provides critical insights into questions of attunement, language, the body, and historicity in Heidegger's thinking.